USABILITY AND USER EXPERIENCE TESTING OF THE THREADS APPLICATION USING THE SYSTEM USABILITY SCALE (SUS) AND USER EXPERIENCE QUESTIONNAIRE (UEQ): PENGUJIAN USABILITY DAN USER EXPERIENCE APLIKASI THREADS MENGUNAKAN SYSTEM USABILITY SCALE (SUS) DAN USER EXPERIENCE QUESTIONNAIRE (UEQ) - Anggraini, Ayu; Suyatno, Dwi Fatrianto (Universitas Negeri Surabaya, 2024)
Technology now plays an important role in life. So the progress of information technology is also accelerating rapidly. The latest data from the central statistics agency shows a fairly high increase in internet usage in Indonesia which can reflect the openness of the community to new technologies. From people's openness to new technology, mobile apps have become popular, one of which is the Threads application. Meta claims that Threads attracted 100 million users within a week of its launch. However, reports from online research researchers such as Sensor Tower and SimiliarWeb show that the number of Threads users has decreased significantly. On the other hand, usability and user experience are important elements in application development. The use of SUS and UEQ measurement tools allows users to test the usability and user experience of an application from the end user's perspective based on the experience after using the application. Based on the results of data processing using the System Usability Scale (SUS), the results of the calculation in the form of the number of average score values of 54.35 enter the Grade Scale with category D, Adjective Range with category OK, Acceptable with category Marginal, and NPS (Net Promoter Score) with category Ditractor. Based on the results of data processing using the User Experience Questionnaire (UEQ), the value of attractiveness (mean 0.4), perspicuity (mean 0.605), efficiency (mean 0.15), dependability (mean 0.065), stimulation (mean -0.095), and novelty (mean -0.155) has an average value between -0.8 and 0.8, which indicates a neutral evaluation level. Based on the benchmark results, the value obtained on each UEQ variable using the UEQ Data Analysis Tool gets a Bad value on all variables, namely attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty. Overall, based on the user experience after using the Threads application, it is rated less by respondents so it needs to be improved to meet user expectations.